Peatland management without burning: alternative restoration efforts in (re)wet peatlands - Gunawan, Haris; Afriyanti, Dian; Humam, Ivan A; Nugraha, Fajar C; Wetadewi, Rahmawati I; Surayah, Lutfiah; Nugroho, Adi; Antonius, Sarjiya (Jurnal Pengelolaan Sumberdaya Alam dan Lingkungan (Journal of Natural Resources and Environmental Management), 2020)
The last two decades, peatland management has resulted in susceptibility of peatlands to fires due to peat degradation associated with drainages, climate, and culture in opening peatlands. Rewet peatlands is the ultmate goal of peat restoration. Nevertheless, the needs for production in peatlands require a milestone to bridge the measure to restore peatlands hydrologically. Peatland management without fires is a method, and the combination with methods to supply nutrient in wet/moist/anaerobic peatlands would be innovative technology. It is aimed to provide nutrients of organic materials without stimulating decomposition of peat materials. Along with restoration measure hydrologically, agriculture in cultivation zone of peatlands shall consider water-zone as a specific and small unit within a wide peat hydrological unit.